European lessons on consolidation in banking - Boot, Arnoud W.A. (Journal of Banking & Finance, 1999)
Does Europe offer lessons for the consolidation in US banking? In this paper, it is argued that the political dimension in Europe has led to the protection of national flagships and consolidation mainly on a national scale. Lessons for the US are limited. Rather, the regional expansion observed in US banking may offer valuable lessons for imminent cross-border mergers in European banking.